2012
DOI: 10.2147/tacg.s21953
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of schizophrenia genetics: genetic diagnosis, risk, and counseling in the molecular era

Abstract: Schizophrenia is a complex neuropsychiatric disease with documented clinical and genetic heterogeneity, and evidence for neurodevelopmental origins. Driven by new genetic technologies and advances in molecular medicine, there has recently been concrete progress in understanding some of the specific genetic causes of this serious psychiatric illness. In particular, several large rare structural variants have been convincingly associated with schizophrenia, in targeted studies over two decades with respect to 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 282 publications
0
14
0
Order By: Relevance
“…Parents of children with 22qDS and individuals with the condition themselves cite consultation with specialists as one of the benefits of a genetic diagnosis [Costain et al, 2011]. It has also been suggested that the greatest potential benefit of early diagnosis of 22qDS is the ability to recognize the early stages of schizophrenia or other psychiatric illness, allowing prompt consultation or diagnosis from experts, followed by effective treatment [Bassett and Costain, 2012]. Clinical practice guidelines for the management of patients with 22qDS recommend repeated psychiatric assessments beginning as early as age 1, suggesting medical providers pay vigilant attention to changes in behavior or emotional state [Bassett et al, 2011;Habel et al, 2011].…”
Section: Resultsmentioning
confidence: 99%
“…Parents of children with 22qDS and individuals with the condition themselves cite consultation with specialists as one of the benefits of a genetic diagnosis [Costain et al, 2011]. It has also been suggested that the greatest potential benefit of early diagnosis of 22qDS is the ability to recognize the early stages of schizophrenia or other psychiatric illness, allowing prompt consultation or diagnosis from experts, followed by effective treatment [Bassett and Costain, 2012]. Clinical practice guidelines for the management of patients with 22qDS recommend repeated psychiatric assessments beginning as early as age 1, suggesting medical providers pay vigilant attention to changes in behavior or emotional state [Bassett et al, 2011;Habel et al, 2011].…”
Section: Resultsmentioning
confidence: 99%
“…For total parental inheritance, significantly (p<0.0001) more BP4-BP5 deletions were transmitted maternally (n=51, 73.9%) than paternally (n=18, 26.1%). Five cases had an additional genetic aberration that may be contributing to their phenotypes, including 16q duplications [37, 8], and mosaic Turner syndrome [39] (Table II). …”
Section: Phenotypes Associated With Changes In Chrna7 Copy Numbermentioning
confidence: 99%
“…Autism and schizophrenia are common neurological disorders that are estimated to affect 1% and 0.75% of the worldwide population, respectively (Bassett & Costain, ). Whereas both disorders are highly polygenic, microarray and exome sequencing studies have enabled the discovery of multiple highly penetrant genetic risk factors in these disorders, including rare inherited and de novo single nucleotide variants (SNVs; De Rubeis et al, ; Genovese et al, ; McCarthy et al, ; Mowry & Gratten, ; O'Dushlaine et al, ; O'roak et al, ; Sklar et al, ; Wormley et al, ) and copy number variations (CNVs; De Rubeis & Buxbaum, ; Szatkiewicz et al, ).…”
Section: Introductionmentioning
confidence: 99%